A STUDY OF PRE-SEQUENCES IN REQUESTS IN ENGLISH VERSUS VIETNAMESE - Nguyễn Thị Kim Cúc (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Pre-sequences are an interesting and common fact of language. They are used much in human daily communicative process and widely applied for many speech acts. This research offers an analysis of pre-sequences in requests in English and Vietnamese. The aims of this study are to examine pre-sequences in requests and find out similarities and differences of pre-sequences in requests in English and Vietnamese. In addition, the study suggests some implications of finding for the teaching and learning English as a foreign language in Vietnam. The study is executed in a contrastive analysis of pre-sequences in requests in English and Vietnamese. In order to obtain these aims, a quantitative method, a qualitative method and a descriptive method are taken into account. The study focuses on the investigation of the syntactic and functional representations of pre-sequences in requests in English and Vietnamese based on the research data collected from English and Vietnamese conversational books short stories and novels.